1968
DOI: 10.17741/bgsf/40.003
|View full text |Cite
|
Sign up to set email alerts
|

Structural position of ore-bearing areas in Finland

Abstract: The Finnish ore deposits of the economically most important metals -mainly Cu, Fe, Ni, Pb, Ti and Zn -are grouped according to their metal content. This grouping closely follows the genetic classification of the ore deposits. A really the ore deposits in Finland are concentrated into four elongated zones, each of which probably contains several metallogenic provinces. The location of the zones shows a close relationship to structural features, especially fault zones and to the location of basic intrusive rocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1970
1970
1981
1981

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…3) which separates it from areas of higher uplift northeast of the trough. This gravity trough, attributed to deep faults by several authors (Paarma and Marmo 1961, Mikkola and Niini 1968, Talvitie 1971, zigzags in line with four of the main trends (I-IV) described. The zigzags coincide with long faults belonging to these trends.…”
Section: Distribution Of Land Upliftsupporting
confidence: 75%
See 2 more Smart Citations
“…3) which separates it from areas of higher uplift northeast of the trough. This gravity trough, attributed to deep faults by several authors (Paarma and Marmo 1961, Mikkola and Niini 1968, Talvitie 1971, zigzags in line with four of the main trends (I-IV) described. The zigzags coincide with long faults belonging to these trends.…”
Section: Distribution Of Land Upliftsupporting
confidence: 75%
“…3); it is indicated partly by main and partly by subordinate maxima of the rosettes. Numerous Ni-Cu sulfide deposits, associated with basic and ultrabasic plutonic rocks, are aligned with this zone, which is characterized by wide drag folds upon steep axes, and by traces of repeated brecciation (Mikkola and Niini 1968, Talvitie 1971, Gaäl 1972. The zone is seismically active (Fig.…”
Section: Shear Zonesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Wahl (1963), the zone, which was later suggested to be potential for Ni-Cu ores, is characterized by hypersthenebearing plutonites, the emplacement of which was controlled by two fracture lines trending NW-SE. The concept of the ore potentiality of the »Ladoga-Bothnian Sea zone» was originally proposed by Paarma and Marmo (1961); it was later corroborated by Mikkola and Niini (1968), Mikkola (1971) and Kahma (1973). Gaål (1972) suggested that the intrusives that act as host rocks for the nickel ores are associated with transcurrent faults, domes and brachyantiforms.…”
Section: Geology Of the Environmentmentioning
confidence: 98%
“…Gaål (1972) suggested that the intrusives that act as host rocks for the nickel ores are associated with transcurrent faults, domes and brachyantiforms. Fault-tectonic analyses on the Ladoga-Bothnian Sea zone have been undertaken by Härme (1961) and Salli (1970), and lineament interpretations by Talvitie (1971), and Mikkola and Vuorela (1977). Parkkinen (1975) maintains that the intrusives were emplaced during large-scale regional movements.…”
Section: Geology Of the Environmentmentioning
confidence: 99%